Rational construction of PCL-PEG/CS/AST nanofiber for bone repair and regeneration - Cao, Zhengyu; Zhuo, Hongwu; Zhu, Wendong; Peng, Xiangfang; Li, Jian (Frontiers in Bioengineering and Biotechnology, 2025)
Humerus greater tuberosity (HGT) avulsion fracture is one of the most common types of proximal humerus fractures. The presence of motion and gap lead to the failure of implants, due to the force pulling from the supraspinatus. In this work, electrospinning technology was applied to fabricate PCL-PEG/CS/AST nanofiber with superior biocompatibility and mechanical property. Furthermore, PCL-PEG/CS/AST nanofiber could promote proliferation and osteogenic differentiation of bone mesenchymal stem cells (BMSCs) in vitro. We believe that this work indicates a promising way to promote the union of HGT avulsion fractures by using PCL-PEG/CS/AST nanofiber.